PEMETAAN DAN ANALISIS SEBARAN SPBU DI KOTA BANDAR LAMPUNG TAHUN 2015 - I Kadek Agus Setiawan; I Gede Sugiyanta; Dedy Miswar (JPG (Jurnal Penelitian Geografi), 2015)
The objective of this research was to analyze the gas pump station distribution in Bandar Lampung. The analysis of this research included (1) distance average of amongst gas pump stations in Bandar Lampung, (2) distribution pattern of gas pump stations in Bandar Lampung, and (3) types of gas pump stations besed on their codes in Bandar Lampung. This was a survey research. The research results showed that (1) the average distance between gas pump station was 2.70 km, and this was categoriezed as close distance, (2) distribution pattern showed that gas pump stations were evenly distributed in Bandar Lampung, (3) types of gas pump stations besed on their codes showed that there were 3 gas pump stations with COCO codes, and 30 gas pump stations with DODO codes.Penelitian ini bertujuan untuk menganalisis sebaran SPBU di Kota Bandar Lampung. Analisis dalam peneitian ini meliputi (1) Jarak Rata-rata SPBU satu dengan yang lainnya di Kota Bandar Lampung. (2) Pola sebaran SPBU yang ada di Kota Bandar Lampung. (3) Jenis-jenis SPBU berdasarkan kodenya di Kota Bandar Lampung. Penelitian ini menggunakan metode penelitian survei. Dari hasil penelitian diketahui 1) Jarak rata-rata antar SPBU di Kota Bandar Lampung didapatkan 2,70 km yang dikategorikan Dekat. 2) Pola sebaran SPBU di Kota Bandar Lampung merata. 3) Jenis-jenis SPBU berdasarkan kodenya yaitu didapatkan 3 SPBU dengan jenis COCO dan 30 SPBU dengan jenis DODO.Kata Kunci : pemetaan, sebaran, jenis, SPBU.